Analisis Variabel Penentu Pendapatan Perkapita Sebagai Upaya Pencegahan Growth Slowdown (Studi di China, Filipina, India, Indonesia, Malaysia, dan Thailand) - Lubis, Raisal Fahrozi (Jurnal Ilmiah Mahasiswa FEB, 2014)
The rapid growthexperienced byAsian countriesin thepast decadehad raisedsomeAsian countriesrose tomiddle-income countries. However, it does not meanthateconomic developmentshave been successful, sincethe purposeof economic developmentis to improve thewelfare of the communityitselfwitha highstandardofliving, or becomea high-income country.The success ofeconomic developmentto Â becomedeveloped countryis a hardworksincestudies have shownfrom101countries that haveachieved middle incomecountries statusin 1960, only 13countriesable totransition becomehigh-income countries.The phenomenon ofthese countriesto be unsuccsessful transitionto becomehigh-income countriesoftencounted bythe termof middle incometrap.Some countries thathaveindicatedstuck ina middle incometrapisthe LatinAmerican countriesin general, whilethe countries thatmanaged toescapingthis threatisthe Asian tigercountriessuch asJapan, SouthKorea, Hong Kong, Singapore, andTaiwan.Some studies said that the middle income trap can be explained by a significant slowdown in the growth of some middle-income countries. Therefore, this studywilldiscusson variables thathave a significant influenceon the some countrie`s GDP percapita.Some determinantvariables of income percapita to be discuss is aexpenditure shares factors, human capital factors, demography, high technology exports, and the exchange rate. With panel data regression analysis, this study will be able to explain the effect of each variable. It will be focuss on some Asian developing countries such as China, India, Indonesia, Malaysia, the Philippines, and Thailand and thestudyperiodis1997 to2011.Understandingonthe effectofdeterminantvariables of income percapitacan be formulatedseveralpolicy recommendationsthatshould betaken to ensure thatthese countriesable toavoid the slowdwongrowth. Keywords :middle income countries, middle income trap, growth slowdwon, determinant variables of income percapita, panel data.